Intraoperative Optical Coherence Tomography Analysis of Clear Corneal Incision: Effect of the Lateral Stromal Hydration - Jiri Cendelin; Stepan Rusnak; Lenka Hecova (Journal of Ophthalmology)
Aim of the Study. The aim of this prospective study was to analyse the effect of lateral stromal hydration on the morphology of clear corneal incision architecture using the microscope integrated anterior segment OCT. Methods. The cohort included 65 clear corneal incisions of 49 patients who underwent cataract surgery. Corneal incisions were recorded using a Leica Proveo 8 microscope with an intraoperative OCT EnFocus™ device continuously during the surgery. Corneal incision morphology before and after lateral stromal hydration was analysed. Results. Good adaptation of the corneal incision before hydration was present in 39 cases (60%), in 16 cases (24.6%), the prominence of posterior lip was present, and, in 10 cases (15.4%), the posterior lip tongue was inverted/retracted into the incision. In 38 cases (58.5%), hydration had no effect on the incision architecture; most often, it was primarily a well-adapted corneal incision (46.2%), less often an incision with posterior lip prominence (10.8%), or tongue inversion into the incision (1.6%) prior to hydration. Hydration worsened the incision architecture in 14 cases (21.5%); most often, it induced/worsened posterior lip prominence (15.4%), less often posterior lip retraction (1.6%), tongue inversion into the incision (1.6%), gap development in the peripheral part of the corneal incision (1.6%), or incomplete opening of the corneal incision (1.6%). In 13 cases (20%), hydration improved the incision architecture, especially in cases with inverted or retracted posterior lip tongue (12.3%), less often in cases with posterior lip prominence (7.7%). Conclusion. Lateral stromal hydration seldom affects the condition of the corneal incision. Still, it can cause both deterioration and improvement of the corneal incision architecture. Intraoperative OCT provides real-time monitoring of corneal incision morphology during hydration procedure.